USING ARTIFICIAL INTELLIGENCE AND BLOCKCHAIN DIGITAL TECHNOLOGY IN ACCOUNTING WITH THE AIM OF INCREASING TRANSPARENCY AND EFFICIENCY - Shurooq Hammood Abdulhussin Albdir; Ahlam magtoof alwan (Scholars Digest Publishing, 2024)
Today, digital technology has entered various sciences and has led to the growth of their efficiency. In this research, using a quantitative-qualitative method, the effect of using digital technology such as artificial intelligence and blockchain in the accounting process was studied with the aim of increasing transparency and efficiency. The accountants' society of Iraq, as the accountants' union, was chosen as the statistical society. Sampling was accessible and purposeful. In the quantitative part, ten people and in the qualitative part one hundred people agreed to cooperate, and there were no common members between the two communities. The found factors include 1. providing suitable software, with sub-factors of simplicity in use, installation, calculations and recording with high reliability; 2. Increasing speed with secondary factors of speed in calculations, recognition of conflicts, timely notification of errors and speed in analysis; 3. Recognizing conflicts with the sub-factors of numerical, qualitative, management and development conflicts and 4. Intelligent calculations with the sub-factors of timely declaration of conflict, periodic declaration of conflict, periodic analysis and reporting in plain language were determined.
Keywords: Accounting efficiency, Transparency, Digital technology, Blockchain, Artificial intelligence.